Characterization of chitin synthase and chitinase gene families from the African malaria mosquito - Zhang, Xin (Kansas State University, 2010)
Chitin metabolism represents an attractive target site for combating insect pests as insect growth and development are strictly dependent on precisely toned chitin synthesis and degradation and this process is absent in humans and other vertebrates. However, current understanding on this process and the involved enzymes is rather limited in insects. In this study, two chitin synthase genes (AgCHS1 and AgCHS2 or AgCHSA and AgCHSB), and 20 chitinase and chitinase-like genes (groups I-VIII) presumably encoding the enzymes for chitin biosynthesis and degradation, respectively, were identified and characterized in African malaria mosquito, Anopheles gambiae. Immunohistochemistry analysis and developmental stage- and tissue-dependent transcript profiling by using reverse transcription PCR, real-time quantitative PCR, and in situ hybridization revealed new information on these genes. Current understanding on chitin synthases is extended by the expression profiles such as the localization of AgCHS1 and AgCHS2 transcripts in eggs, AgCHS2 transcripts in the posterior larval midgut, AgCHS1 and AgCHS2 proteins in the compound eyes, and AgCHS2 enzyme in pupal inter-segments. Chitinase and chitinase-like genes are highly diverse in their gene structure, domain organization, and stage- and tissue-specific expression patterns. Most of these genes were expressed in several stages. However, some genes are stage- and tissue-specific such as AgCht8 mainly in pupal and adult stages, AgCht2 and AgCht12 specifically in foregut, AgCht13 exclusively in midgut. Functional analysis of each chitin synthase gene was conducted by using the chitosan/dsRNA nanoparticle-based RNA interference (RNAi) through larval feeding. The repression of the AgCHS1 transcripts which are predominantly expressed in carcass initiated from the mosquito larval feeding of dsRNA suggests the systemic nature of RNAi in mosquito larvae. In addition, silencing of AgCHS1 increased larval susceptibilities to diflubenzuron, whereas silencing of AgCHS2 enhanced the peritrophic matrix disruption and thus increased larval susceptibilities to calcofluor white or dithiothreitol. Furthermore, a non-radioactive method was adapted and optimized to examine the chitin synthase activity in mosquitoes. By using this method, diflubenzuron and nikkomycin Z show limited in vitro inhibition on chitin synthase at high concentration in cell free system, whereas no in vivo inhibition was observed.
Keywords: Chitin synthase; Chitinase; Anopheles gambiae; Larval RNA interference; Chitin synthase activity; Diflubenzuron; Biology, Entomology (0353); Biology, Molecular (0307); Chemistry, Biochemistry (0487)